2006
DOI: 10.1159/000092865
|View full text |Cite
|
Sign up to set email alerts
|

Lung Disease and Brain Development

Abstract: With the technical progress made in fetal and neonatal intensive care, perinatal mortality has decreased by 25% over the last decade and has expanded the surviving premature population. Prematurity drastically changes the environment of the developing organism. Striking evidence from a number of disciplines has focused attention on the interplay between the developing organism and the circumstances in which it finds itself. The environmental event during a sensitive period in development, induces injury and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 187 publications
0
1
0
1
Order By: Relevance
“…35,36 Hüppi et al demonstrated that developmental disruption and plasticity in the lungs and brain was closely associated with events inducing inflammation, oxidative stress, and endocrine disruption. 37 These events could disturb NAA production in neuronal mitochondria, 32,33 leading to reductions in tNAA concentrations in subjects with low DQ scores.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Hüppi et al demonstrated that developmental disruption and plasticity in the lungs and brain was closely associated with events inducing inflammation, oxidative stress, and endocrine disruption. 37 These events could disturb NAA production in neuronal mitochondria, 32,33 leading to reductions in tNAA concentrations in subjects with low DQ scores.…”
Section: Discussionmentioning
confidence: 99%
“…menyebabkan perkembangan kematian sel, dan IL-6 juga menyebabkan gliosis reaktif melalui aktivasi mikroglia Kadar IL-6, TNF α adalah merupakan sitokin pro inflamasi atau astrosit sehingga menyebabkan terjadinya yang diperiksa bila telah terjadi tanda SIRS. Kadar IL-6 dan astrositosis dan keterlambatan mielinisasi pada kerusakan TNF-α diperiksa dengan cara ELISA menggunakan kit materi putih pada bayi sangat premature (5)(6)(7)(8).…”
Section: Pendahuluanunclassified